(untitled) (Journal of Plant Disease Sciences, 2025)
Wilt/root rot complex of chickpea is a major constraint in chickpea production. Among the fungicides tested, carboxin 37.5% + thiram 37.5% WP, tebuconazole 50% + trifloxystrobin 25% WG, and prochloraz 5.7% + tebuconazole 1.54% ES showed complete radial mycelial inhibition of the pathogens under in vitro conditions. Among the bioagents, Trichoderma harzianum showed maximum inhibition (84–85%) under in vitro conditions. Under in vivo conditions, integrated treatments involving seed treatment and multiple soil applications of Trichoderma harzianum along with the fungicide prochloraz 5.7% + tebuconazole 1.54% ES resulted in the lowest disease incidence (18.70% at 60 DAS). These results suggest that integrated seed and soil treatments with the bioagent Trichoderma harzianum at 4 g kg⁻¹ of seed and the fungicide prochloraz 5.7% + tebuconazole 1.54% ES at 2 ml kg⁻¹ of seed offer promising management of the chickpea wilt/root rot complex.